Risk Factors for Injuries in Runners: A Systematic Review of Foot Strike Technique and Its Classification at Impact. Issue 9 (9th September 2021) - Burke, Aoife; Dillon, Sarah; O'Connor, Siobhán; Whyte, Enda F.; Gore, Shane; Moran, Kieran A.
Background: It has been suggested that foot strike technique (FST) at initial contact is related to running-related injuries (RRIs). Purpose: To explore the relationship between FST and RRIs. Study Design: Systematic review; Level of evidence, 3. Methods: A systematic electronic search was performed using MEDLINE, PubMed, SPORTDiscus, Scopus, and Web of Science databases. Included were studies published in the English language that explored the relationship between FST and RRIs between January 1960 and November 2020. Results were extracted and collated. The Grading of Recommendations, Assessment, Development and Evaluation approach was applied to synthesize the quality of evidence. Results: We reviewed 13 studies exploring the relationship between FST and RRIs. Of these, 6 studies reported FST categorically (foot strike pattern [FSP]), and 7 reported continuous measures (foot contact angle, ankle flexion angle, and strike index). Three of the 6 studies looking at categorical FSP found rearfoot strikers have a significantly greater retrospective injury rate than do non– rearfoot strikers, with 1 other study noting a greater risk associated with midfoot and forefoot strike. Regarding the continuous measures of FST, only 1 of the 7 studies reported a significant relationship with RRIs. Conclusion: There was low evidence to suggest a relationship between FST (or its subcategories of categorical FSP and continuous measures) and RRIs. While two-thirds of the categorical studies found a relationship between FSP and RRIs, these studies were very low quality, with limitations such as retrospective study design, low participant numbers, and poor FSP assessment methods. More large-scale prospective studies are required.